Advanced Functionalized CeO2/Al2O3 Nanocomposite Sensor for Determination of Opioid Medication Tramadol Hydrochloride in Pharmaceutical Formulations - Seham S. Alterary; Maha F. El-Tohamy (Nanomaterials, 2022)
Background: The exceptional characteristics of cerium oxide (CeO2) and aluminum oxide (Al2O3) nanoscales have inspired significant attention to those nanocomposites as possible electroactive resources for applications of sensing and biosensing. Methods: In this research, an innovative new factionalized CeO2/Al2O3 nanocomposite membrane sensor was presented to assess tramadol hydrochloride (TRD) in marketable products. Results: Tramadol-phosphomolybdate (TRD-PM) was formed by mixing tramadol hydrochloride and phosphomolybdic acid (PMA) in the attendance of polymeric matrix and o-nitrophenyloctyl ether solvent mediator. With 1.0 × 10−10–1.0 × 10−2 mol L−1 as a range of linearity and EmV = (57.567 ± 0.2) log [TRD] + 676.29 as a regression equation, the functionalized sensor using TRD-PM-CeO2/Al2O3 nanocomposite showed great selectivity and sensitivity for the discriminating and measurement of TRD. Using the regression equation EmV = (52.143 ± 0.4) log [TRD] + 431.45, the unmodified coated wire sensor of TRD-PM, on the other hand, showed a Nernstian response between 1.0 × 10−6 and 1.0 × 10−2 mol L−1, Using the methodology’s specified guidelines, the proposed improved potentiometric system was validated against several criteria. Conclusion: The suggested method is suitable for the determination of TRD in its products.